Low Prevalence of Helicobacter Pylori Infection in Canadian Children: A Cross-Sectional Analysis. (2008) - Segal, Idit; Otley, Anthony; Issenman, Robert; Armstrong, David; Espinosa, Victor; Cawdron, Ruth; Morshed, Muhammad G; Jacobson, Kevan
Abstract : BACKGROUND: The incidence and prevalence rates of childhood Helicobacter pylori infection vary greatly by nation, with infection rates of 8.9% to 72.8% reported in developed and developing countries, respectively. To date, few studies have assessed the prevalence of H pylori in Canadian children, with studies limited to Aboriginal communities and single tertiary care centres from Ontario and Quebec. OBJECTIVES: To determine the prevalence of H pylori in consecutive children referred to three Canadian tertiary care academic centres for upper gastrointestinal (GI) endoscopy due to upper GI symptoms, and to determine the sensitivity and specificity of the carbon-13-labelled urea breath test, the rapid urease test and the H pylori stool monoclonal antigen test. RESULTS: Two hundred four patients were recruited. The prevalence of H pylori was 7.1%. Of the H pylori -positive patients, 41.7% were male, with a mean age of 10.3 years. Ethnic minorities accounted for 42% of the H pylori -positive patients. Consistent with previous observations, the sensitivity and specificity of the carbon-13-labelled urea breath test were 1.0 and 0.98, respectively. The sensitivity and specificity of the rapid urease test were 1.0 and 0.99, respectively. Stool samples were collected from 34 patients from one centre, with a sensitivity and specificity of 1.0 and 0.68, respectively. No defining symptoms of H pylori infection were evident and no peptic ulcer disease was demonstrated. CONCLUSION: H pylori infection rates in Canadian children with upper GI symptoms are low, and are lower than those reported for other developed countries. Further studies are required in Canada to determine the prevalence in the general population and specifically in the populations at risk.